(untitled) (Journal of Public and Nonprofit Affairs, 2021)
This study examines how NPO/NGO-related themes and theories are incorporated into public administration education in South Korea. By analyzing NPO/NGO-related courses in selected public administration programs, this research breaks down their curricula into major categories from the public administration and policy standpoints. This study found that civil society constitutes the public administration environment on the macro-level, while NPO/NGOs are key actors in the participatory governance and contracting-out on the micro-level. From the public policy standpoint, the advocacy function of NPO/NGOs took the central role in the public policy formation stage, while their service delivery function was highlighted in the public policy implementation stage. South Korean PA education is evaluated to take a top-down-style approach in embracing the roles of NPO/NGOs in the public policy implementation process. This study contributes to strengthening ties between PA education and NPO/NGO education and practices.